Degenerative Joint Scoring System - An Ortho-Rheumatological assessment tool - Manish Khanna; Preethi Selvaraj; Madhan Jeyaraman; Sathish Muthu; Venus Khanna (Elsevier, 2022)
Introduction: The most prevalent kind of arthritis in both developed and developing countries is osteoarthritis. Although many scales have been developed worldwide highlighting the importance of lifestyle interventions, very few scales have been constructed from developing countries and no scale has been developed in India. This study aims to develop a scale to assess osteoarthritis and describing the reliability, the validity of the instrument named Degenerative Joint Scoring System (DJSS). Material and methods: The objective of this study was to develop and validate the scale to find out osteoarthritis. Epi info CDC sample size calculator was used to estimate the sample size. A total of 1120 study participants were present in our study to assess the sensitivity of the DJSS. Exploratory factor analysis was performed to assess the internal consistency of the scale. Content validity, construct validity, reliability, and yield were estimated. Results: The scale-content validity index S-CVI/Average for the overall three constructs is 0.94. The reliability of the questionnaire was tested using Cronbach's alpha which was 0.9 and the intraclass correlation coefficient was 0.93; 95% CI (0.85, 0.96) (P < 0.001). The test-retest reliability was assessed showing r = 0.92. The Kaiser-Meyer-Olkin index was 0.805 for the adequacy of samples (Bartlett's test of sphericity was significant, df = 105, P < 0.001). As per the DJSS, 0-5 indicates possible osteoarthritis, 6-10 indicates probable osteoarthritis and 11-15 indicates definite osteoarthritis. Conclusion: DJSS can help orthopaedicians, physiotherapists, and academics and researchers on the diagnosis of arthritis easily and recovery accessible. This instrument needs to be generalized by tracking the real outcomes of patient-reported outcome interventions from developed countries.